2019
DOI: 10.1186/s12931-019-1043-9
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of death or lung transplant after a diagnosis of idiopathic pulmonary fibrosis: insights from the IPF-PRO Registry

Abstract: Background Idiopathic pulmonary fibrosis (IPF) is a progressive disease with a variable clinical course and high mortality. We used data from a large national US registry of patients with IPF to investigate relationships between patient characteristics, including markers of disease severity, and mortality. Methods The analysis cohort comprised patients enrolled in the IPF-PRO Registry from its inception on 5 June 2014 to 26 October 2017. The primary criterion for inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
48
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 31 publications
(35 reference statements)
11
48
0
1
Order By: Relevance
“…A wealth of data has demonstrated that low FVC and/or low DLco are risk factors for acute exacerbations in patients with IPF [11,32,33], possibly because patients with more advanced disease are more vulnerable to insults such as infection that may lead to an acute exacerbation [11]. Similarly, the risk of mortality was higher in patients with more severe impairment in DLco in the INSTAGE trial than in patients in the INPULSIS trials, consistent with previous studies identifying low DLco as a risk factor for mortality in patients with IPF [4,33,34].…”
Section: Discussionsupporting
confidence: 83%
“…A wealth of data has demonstrated that low FVC and/or low DLco are risk factors for acute exacerbations in patients with IPF [11,32,33], possibly because patients with more advanced disease are more vulnerable to insults such as infection that may lead to an acute exacerbation [11]. Similarly, the risk of mortality was higher in patients with more severe impairment in DLco in the INSTAGE trial than in patients in the INPULSIS trials, consistent with previous studies identifying low DLco as a risk factor for mortality in patients with IPF [4,33,34].…”
Section: Discussionsupporting
confidence: 83%
“…Studies in patients with progressive fibrosing ILDs have identified several factors that predict mortality, but these need to be interpreted carefully given the variation in the methodology used and the retrospective nature of most of the studies. Lower FVC is an established predictor of mortality in patients with progressive fibrosing ILDs, as evidenced by numerous studies spanning IPF [55][56][57], RA-ILD [4,49], SSc-ILD [58][59][60], chronic HP [61,62] and fibrotic iNSIP [53]. The same is true of DLco [55,56,60,[63][64][65], although this is harder to assess in multi-center studies due to a lack of standardization in its measurement.…”
Section: Predictors Of Disease Progression In Patients With Fibrosingmentioning
confidence: 99%
“…Previous qualitative research with patients and caregivers suggests that although supplemental oxygen use may improve activity and physical function, it may also negatively affect QOL by prohibiting patients from living "normal lives." 32 Given that supplemental oxygen use was associated with worse survival in the IPF-PRO registry, 33 oxygen use may also be a marker for underlying disease severity that negatively affects health-related QOL. Finally, given that the AmbOx trial was conducted in a single tertiary center in the United Kingdom, the findings may not be generalizable to real-world, multicenter registry populations such as included in the IPF-PRO registry.…”
Section: Discussionmentioning
confidence: 99%